The Effect of Providing Health Education on Stunting Prevention to Toddlers Through PreExperimental Research with a One Group Pretest Posttest Approach on the Level of Knowledge in Banjaran Village Posyandu Cadres - Al Imron, Muhammad Istio Hadi; Syadza, Lailatus; Surur, Idcholus (Journal of Health Community Service, 2023)
Stunting is a chronic nutritional problem due to a lack of nutritional intake for a long period of time, resulting in impaired growth in children. Prevention of this problem is still being sought, because the stunting rate is still high until now, especially in the environment in Banjaran village, Driyorejo Gresik district. The purpose of this counseling or education is so that mothers get enough knowledge to overcome stunting in toddlers. The implementation of this counseling activity is attractive, where participants are asked to answer questions from the presenter that have been given in the question answer sheet, in each question there will be a discussion related to this given by the speaker later. The results and discussions of the average score before and after counseling were 67, while the score after counseling was obtained on average 77.5. Results obtained with a p-value of 0.001 then H0 rejected. So it can be concluded that there is The effect of providing counseling or education on stunting prevention to toddlers through the One Group Pretest Posttest approach to Posyandu Toddler cadres in Banjaran village, Driyorejo District, where there is an increase in the knowledge of Posyandu toddler cadres related to stunting prevention in toddlers by 15% before and after counseling and education is given.